EFEKTIVITAS PEMERIKSAAN PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA PARE-PARE - Muhammad Adil; Naidah Naidah; Dian Rahayu (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study is to measure the level of effectiveness of tax audits based on SP2 and based on the realization of tax audit receipts. This research uses descriptive research with a qualitative approach. The location of this research is KPP Pratama Parepare. The results of this study indicate that the level of effectiveness of tax audits based on SP2 at KPP Pratama Parepare from 2014 to 2018 is in the very effective category. The level of effectiveness of tax audits based on SKP at KPP Pratama Parepare in 2014 was included in the ineffective criteria, 2015 included in the ineffective criteria, 2016 included in the ineffective criteria, 2017 included in the ineffective criteria, 2018 included in the very effective criteria. Factors that affect the effectiveness of tax audits include the attitude of taxpayers, tax auditors, short tax audit time, taxpayer psychology, office facilities, communication, as well as support from leaders and good cooperation between divisions.